Persepsi Ibu Rumah Tangga terhadap Pembelian Kerupuk di Kota Banjarbaru - Reny Wijayanti; Nina Budiwati; Djoko Santoso (Universitas Lambung Mangkurat, 2012)
The study is aimed to know the consumer decision choice on cracker related to price, income level, occupation and ethnicity; to know the most favorite cracker; and to know housewives perception on cracker quality in Banjarbaru Municipality. Primary and secondary data were used in the study. Respondents were selected through multistage random sampling.In Banjarbaru, there are 7 types of crackers available based on its specific ingredient, i.e.: shrimp, fish, rambak (cowhide), wheat, onion, terasi (fermented shrimp), and sweet potato. The level of preference from the highest are shrimp cracker, followed by fish, rambak, onion, and wheat cracker. Terasi and sweat potato are the less favorite cracker.Coefficient correlation of Spearman’s rank was used to know housewives perception on cracker quality. The coefficient is 8.99 and significant, which mean that there is a positive correlation between the housewives perception and cracker quality.